Description of oral motoric disorders in 2-4 years old children - Sabilah, Rossa Ayu; Primarti, Risti Saptarini; Riyanti, Eriska (Universitas Padjadjaran, 2016)
Introduction: Oral motor disorders, such as speech and swallowing disorders, often occur in children. Generally parents complain that children refuse to eat hard food, drooling excess, and unable to speak clearly. Oral motor disturbance can occur due to the unavailability of maturation of oral motor structure. This study was aimed to determine the description of oral motor disturbance in children aged 2-4 years in some Integrated Health Service (Posyandu) in Bandung. Methods: Descriptive research with cross sectional design. The study was conducted on 100 parents who came to six posyandu in Bandung by using questionnaires through guided interviews by researchers. Samples were taken using multistage random sampling technique. The results will be presented in tabular form and assessed using Arikunto standard criteria. Results: The results showed a low percentage in oral motor disturbances. Indicators of oral motor disturbance in children aged 2 - 4 years included in either category. As for children who have oral motor disorders exhibit various manifestations. Conclusion: The description of oral motor disorders in children aged 2 - 4 years in Posyandu in Bandung was shown by various manifestations. Based on the number of populations taken, oral motor disorders in children aged 2-4 years included into either category.